Identifying Protein Complexes With Clear Module Structure Using Pairwise Constraints in Protein Interaction Networks - Liu, Guangming; Liu, Bo; Li, Aimin; Wang, Xiaofan; Yu, Jian; Zhou, Xuezhong (Frontiers in Genetics, 2021)
The protein-protein interaction (PPI) networks can be regarded as a powerful platform to elucidate the principle and mechanism of cellular organization. Uncovering protein complexes from PPI networks will lead to better understanding the science of biological function in cellular systems. In recent decades, numerous computational algorithms have been developed to identify protein complexes. However, majority of them primarily concern on topological structure of PPI networks and lack of the consideration for the native organized structure among protein complexes. The PPI networks generated by high-throughput technology include a fraction of false protein interactions which make it difficult to identify protein complexes efficiently. To tackle these challenges, we propose a novel semi-supervised protein complex detection model based on non-negative matrix tri-factorization, which not only considers topological structure of a PPI network but also makes full use of available high quality known protein pairs with must-link constraints. We propose non-overlapping (NSSNMTF) and overlapping (OSSNMTF) protein complex detection algorithms to identify the significant protein complexes with clear module structures from PPI networks. In addition, the proposed two protein complex detection algorithms outperform a diverse range of state-of-the-art protein complex identification algorithms on both synthetic networks and human related PPI networks.